STUDENTS’ PERCEPTIONS AND LEARNING INTEREST AS DETERMINANTS OF ENGLISH SPEAKING ABILITY IN AI-ASSISTED AND QUIZIZZ-BASED LEARNING ENVIRONMENTS - Rindika Pramadanti; Rudhi Achmadi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
This study explored the implementation of AI-Assisted Learning and Quizizz-Based Learning in enhancing students’ English speaking ability in the EFL classroom at Universitas Asaindo. It also examined how learning interest and students’ perceptions emerged through the integration of these technology-enhanced learning approaches. A qualitative case study design was employed involving 18 first-semester undergraduate students and one English lecturer. Data were collected from students and the lecturer through interviews and classroom observations supported by relevant documentation. The data were analyzed in depth to obtain a comprehensive understanding of participants’ experiences in using AI-Assisted Learning and Quizizz-Based Learning.The findings indicated that AI-Assisted Learning improved students’ speaking ability by providing personalized feedback, pronunciation correction, and opportunities for independent speaking practice. Students reported increased confidence, fluency, and willingness to communicate in English. In addition, Quizizz-Based Learning enhanced classroom engagement, participation, and learning motivation through gamified features such as points, rankings, and instant feedback. The study also revealed that both learning approaches fostered greater learning interest by creating interactive and enjoyable learning experiences. Furthermore, students expressed positive perceptions toward the use of AI and Quizizz, describing them as useful, accessible, and effective tools for language learning. These positive perceptions and increased learning interest encouraged students to participate more actively in speaking activities. Overall, the integration of AI-Assisted Learning and Quizizz-Based Learning contributed positively to students’ English speaking ability and promoted a more engaging and student-centered EFL learning environment.